General practitioners’ and medical students’ current knowledge and attitudes toward non-pharmacological interventions for dementia - Frankenstein, Lou L.; Pickard, Lea; Franikowski, Philipp; Jahn, Georg (Frontiers in Medicine, 2025)
BackgroundGeneral practitioners in Germany infrequently prescribe effective non-pharmacological interventions for dementia patients. The aim of this study was to investigate general practitioners’ education, knowledge, and experiences as well as attitudes toward non-pharmacological interventions to identify potential strategies for increasing treatment quality.MethodsMedical students (N = 115) and practitioners (N = 19) responded to an online survey about the content of their medical studies regarding dementia and two non-pharmacological interventions, occupational therapy and behavioral therapy. Additionally, practitioners (N = 41) rated their assessment and usage of non-pharmacological interventions compared to pharmacological therapy for individuals with dementia. In-depth, semi-structured interviews were conducted with general practitioners (N = 12) to determine the context factors, beliefs, knowledge, and attitudes influencing prescription decisions.ResultsNon-pharmacological interventions seem to be highly underrepresented in medical education. Pharmacological therapy is reported to be used more often, despite possible negative side effects and despite the proven effectiveness of non-pharmacological treatment. The general practitioners’ attitudes toward behavioral and occupational therapy were heterogeneous, but uncertainty was prevalent regarding budget regulations, and reservations to allocate resources to individuals with dementia became apparent.ConclusionTo help more people with dementia and their caregivers benefit from the positive effects of non-pharmacological interventions, general practitioners need to be better informed about these treatment options.